PERAN UNDANG-UNDANG ORMAS TERHADAP PENYELESAIAN KONFLIK ANTAR ORMAS - Wildhan Indra Pramono; Adis Imam Munandar (Magister Hukum Sekolah Pascasarjana Unida, 2020)
In terms of handling community organization conflicts, the problems of violence and anarchism that arise are generally caused by the lack of readiness and firmness of the government in handling community demands. In addition, the existing Civil Society Organization Laws are weak. As a tangible manifestation of a state run by a state government, the state must play an active role in addressing social conflict that is no longer in line with national goals and ignores the law. In the context of the dissolution of riot organizations and triggers of government conflict, it can also see in detail the legal rules contained in the Ormas Law, using the basic concept of limiting human rights as mandated in the constitution and other laws and regulations, then in circumstances that can cause a concern in the Unitary State of the Republic of Indonesia can use the basic theory of state sovereignty to limit the legitimacy of the existence of a mass organization that can jeopardize state sovereignty.